Return to work after spinal cord injury in Malaysia - Ramakrishnan, K.; Chung, T.Y.; Hasnan, N.; Abdullah, S.J. (Stockton Press, 2011)
Study design:Cross-sectional survey.Objectives:To determine the employment outcomes of persons with spinal cord injury (SCI) and to investigate the impact of various demographic, injury-related and work-related variables on these outcomes.Setting:People living with SCI in Malaysia who are members of a disability support organization.Methods:A total of 84 members of the Malaysian Spinal Injury Association, who have had traumatic SCI for at least 2 years and were between 15 and 64 years of age at the time of study, were interviewed through phone using a questionnaire to identify the association between demographic, injury-related and work-related variables and employment outcomes.Results:The return to work rate in this study was 57.1% (employed at the time of study). The overall employment rate after SCI was 76.2% (worked at some point after injury). Those who were younger at time of injury (<20 years of age), able to drive a modified vehicle, independent in personal care and mobility were positively related to being employed. On the other hand, being hospitalized in the preceding 1 year and receiving financial incentives were negatively related to employment.Conclusion:Functional independence, especially ability to drive, was strongly associated with return to work and should be one of the priority goals of comprehensive rehabilitation of persons with SCI. The negative impact of recent hospitalization as well as financial compensation needs to be probed further.